2019
DOI: 10.1002/bsl.2395
|View full text |Cite
|
Sign up to set email alerts
|

CIT in small municipalities: Officer‐level outcomes

Abstract: Research on the Crisis Intervention Team (CIT) as a method to deal with mental illness in policing encounters has primarily focused on officers from large urban areas. The current study examined officer‐level outcomes in a non‐urban geographical setting using a pre/post‐CIT training design. The sample included 46 police officers from seven departments that would be considered rural and 13 that would be classified as suburban. Officers completed scales to gauge change in mental illness attitudes at the beginnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…When looking to related criminal‐legal professionals, extensive research documents stigma reduction among police officers following crisis intervention team (CIT) training, a 40‐h dynamic training involving education, skills training and exposure to people with mental illnesses who are not in crisis (see Compton et al., 2006; Strassle, 2019), and emergent evidence that CIT can also reduce stigmatising among corrections officers working in prisons (Canada et al, 2020). Probation work is different because it is generally less crisis oriented and there is some evidence that stigma levels vary among criminal–legal professions by organisational factors like working in a participatory workplace (Dir et al., 2019) and individual‐level characteristics like proximity to people with mental illnesses and prior training (Watson et al., 2008).…”
Section: Stigma Mental Illness and Probationmentioning
confidence: 99%
“…When looking to related criminal‐legal professionals, extensive research documents stigma reduction among police officers following crisis intervention team (CIT) training, a 40‐h dynamic training involving education, skills training and exposure to people with mental illnesses who are not in crisis (see Compton et al., 2006; Strassle, 2019), and emergent evidence that CIT can also reduce stigmatising among corrections officers working in prisons (Canada et al, 2020). Probation work is different because it is generally less crisis oriented and there is some evidence that stigma levels vary among criminal–legal professions by organisational factors like working in a participatory workplace (Dir et al., 2019) and individual‐level characteristics like proximity to people with mental illnesses and prior training (Watson et al., 2008).…”
Section: Stigma Mental Illness and Probationmentioning
confidence: 99%
“…The Obama administration's Justice Department endorsed CIT, requiring several major departments to implement CIT training in consent decrees or settlement agreements following police misconduct (Watson, Compton, and Draine 2017). Smaller municipalities (which face statistically higher risks of officer-involved shootings and use of force) are increasingly adapting CIT, as well (Strassle 2019).…”
Section: Crisis Intervention Teams (Cits)mentioning
confidence: 99%
“…In addition to decreasing problematic outcomes, officers in Ellis’ (2014) CIT study reported increased comfort interacting with IMI, as well as more positive attitudes toward this group. More recent research shows that CIT training can reduce stigmatizing attitudes toward mental illness across diverse settings (Strassle, 2019). Tucker et al (2012) observed parallels between community law enforcement and incarceration settings and strongly encouraged implementation of the community CIT model in jails and prisons.…”
Section: Mental Health Training Of Cosmentioning
confidence: 99%